Trend analysis in all-India mackerel catches using ARIMA models - Noble, A; Sathianandan, T V (Indian Journal of Fisheries, 2011)
Annual mackerel landings in India seem lo exhibit a 10-year cycle in long-term fluctuations. To find a suitable forecasting model for it, the annual catch data from 1950 lo 1989 were studied following Box- Jenkins method for lime series analysis, and ARIMA (1,0,0), was identified as the suitable one. Catch predictions by this also hinted at 10-year cycle but seemed to lack seasonal term.